2016
DOI: 10.1002/2016jc011869
|View full text |Cite
|
Sign up to set email alerts
|

Kuroshio subsurface water feeds the wintertime Taiwan Warm Current on the inner East China Sea shelf

Abstract: The Taiwan Warm Current (TWC) has an overwhelming influence on the heat, salt, and nutrients balance on one of the broadest shelf in the world, the East China Sea shelf. In winter, the TWC flows in an unusual upwind direction and reaches the Changjiang (Yangtze River) Estuary, but its origin and pathway are intensely debated. Here combined evidences from current measurement, hydrographic, and stable isotopic data all suggest that the wintertime TWC intrusion off the Changjiang Estuary mainly originates from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 65 publications
(159 reference statements)
2
62
0
Order By: Relevance
“…Both the modeled and observed phosphate concentrations in the bottom layers were higher than surface waters, with values similar to the typical phosphate concentration in the Kuroshio subsurface water (0.7–1.2 μM; Guo et al, ; Zhang et al, ). Previous studies have shown that there is a persistent Kuroshio subsurface water intrusion in the vicinity of the Changjiang River Estuary (Lian et al, ; Yang et al, ). Nevertheless, the simulated bottom phosphate values were ~20% lower than the observed data.…”
Section: Resultsmentioning
confidence: 97%
“…Both the modeled and observed phosphate concentrations in the bottom layers were higher than surface waters, with values similar to the typical phosphate concentration in the Kuroshio subsurface water (0.7–1.2 μM; Guo et al, ; Zhang et al, ). Previous studies have shown that there is a persistent Kuroshio subsurface water intrusion in the vicinity of the Changjiang River Estuary (Lian et al, ; Yang et al, ). Nevertheless, the simulated bottom phosphate values were ~20% lower than the observed data.…”
Section: Resultsmentioning
confidence: 97%
“…This summer Kuroshio subsurface branch was confirmed by field observations and tracer experiments and was named the Nearshore Kuroshio Branch Current (Yang et al, , ). Hydrographic observations of δ 18 O suggested that the KSSW off the northeast of Taiwan could reach as far north as 28°N off the Zhejiang coast via the bottom layer during March 2013 (Lian et al, ). The observed NO 3 − , δ 15 N‐NO 3 − , and δ 18 O indicated that KSSW could extend to the Zhejiang coastal area, after the intrusion onto the ECS northeast of Taiwan from May to June 2014 (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the offshore area northeast of Taiwan, the KSSW contribution can be over 80%, i.e., the water was basically equal to the source water. From northeast of Taiwan to the nearshore area, the KSSW contribution gradually decreased, which suggests that the KSSW mainly intrudes onto the ECS shelf from northeast of Taiwan (Hsueh et al, ; Lian et al, ; Liu et al, ; Tang et al, ; Yang et al, ). Furthermore, another high KSSW contribution core was observed at the offshore area of transect DH4 (∼28.5°N), and the KSSW contribution also gradually decreased shoreward.…”
Section: Resultsmentioning
confidence: 99%